Domestic Violence In Nicola Yoon’s Everything-Everything - Kayetin Defrita Afra Konggang; Sudirman Maca; Asyrafunnisa Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2023)
This study aimed to find out the types of domestic violence orientation on the character and to identify the impact of domestic violence on the victim in Nicola Yoon’s Everything-Everything novel. The data source used in this study were the novel Everything-Everything. This research functional qualitative research as a research method through Psychoanalysis theory by Sigmund Freud as the main theory and psychological of violence by Souto,et.al and definition of Domestic Violence by Mootz,et. al as supporting theory. The result of this study indicated that the writer found 3 types of domestic violence, namely psychological violence of an adult was defined as a verbal or gestural act with the intent to terrorize, humiliate, limit freedom, or isolate an adult from society; manifestation of the violence, the participants was threatened through verbal and non- verbal actions by family members using hurtful situations and imposing their will on adult woman, commonly ignoring the wishes and preferences of the victim; and the impact of psychological violence were the participants expressed sadness, hurt, anger, grief and fear as a result of psychological violence. It also revealed impacts of domestic violence, namely detrimental to the physical health and detrimental to the emotional health.